2018
DOI: 10.3390/nu10111657
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Helianthus tuberosus Ethanol Extract on Dermatophagoides farina body-induced Atopic Dermatitis Mouse Model and Human Keratinocytes

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by complex symptoms. To treat AD without adverse effects, alternative therapeutic agents are required. The tubers of Helianthus tuberosus L. (Jerusalem artichoke) have been used in folk remedies for diabetes and rheumatism. However, its effect on AD development remains unknown. Therefore, this study examined the inhibitory effect of H. tuberosus (HT) on AD skin symptoms using an NC/Nga mouse model and HaCaT keratinocytes. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The interaction of UV radiation with skin chromophores results in excess production of ROS that can interact with DNA, proteins, and other complex organelles inside cells. This can result in DNA mutations, loss of proteins and mitochondria dysfunction affecting keratinocytes and melanocytes and potentially lead to epithelial carcinomas and melanoma, respectively. …”
Section: Introductionmentioning
confidence: 99%
“…The interaction of UV radiation with skin chromophores results in excess production of ROS that can interact with DNA, proteins, and other complex organelles inside cells. This can result in DNA mutations, loss of proteins and mitochondria dysfunction affecting keratinocytes and melanocytes and potentially lead to epithelial carcinomas and melanoma, respectively. …”
Section: Introductionmentioning
confidence: 99%
“…The increase in the level of cytokines released from Th2 cells in AD causes a Th1/Th2 immune imbalance and leads to a lower expression of skin barrier proteins [ 7 ]. It has been reported that damage to the skin barrier function is closely related to AD [ 8 , 9 , 10 , 11 , 12 , 13 ] as it can worsen AD through inflammatory reactions related to AD [ 4 ]. Therefore, the restoration of Th1/Th2 immune balance and skin barrier function is the objective of AD treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the RJ-treated group reduced ear thickness in a dose-dependent manner during the whole study period. Since AD often develops as a systemic immune response, it can affect the immune organs [14,15,16,17]. Therefore, we evaluated that weight of the lymph nodes and spleen was measured in the final week to examine whether the topical application of RJ provided an anti-AD effect in mice.…”
Section: Resultsmentioning
confidence: 99%